2005
DOI: 10.1111/j.1523-1755.2005.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIV-1 genes in podocytes alone can lead to the full spectrum of HIV-1-associated nephropathy

Abstract: The present study demonstrates that podocyte-restricted expression of HIV-1 gene products is sufficient for the development of collapsing glomerulosclerosis in the setting of susceptible genetic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 56 publications
5
98
0
Order By: Relevance
“…For example, the absence of overt nephropathy in mice with podocyte-specific expression of the nef gene may be attributable to the genetic background (C57BL/6J) used (57). Consistent with these data, mice that expressed a HIV-1 transgenes in glomerular podocytes developed HIVAN only in the FVB/N but not the C57BL/6J genetic background (80). These genetic modifiers may be identified by intercrossing that is susceptible to resistant strains.…”
Section: Genetic Susceptibility and Hivansupporting
confidence: 70%
“…For example, the absence of overt nephropathy in mice with podocyte-specific expression of the nef gene may be attributable to the genetic background (C57BL/6J) used (57). Consistent with these data, mice that expressed a HIV-1 transgenes in glomerular podocytes developed HIVAN only in the FVB/N but not the C57BL/6J genetic background (80). These genetic modifiers may be identified by intercrossing that is susceptible to resistant strains.…”
Section: Genetic Susceptibility and Hivansupporting
confidence: 70%
“…This has clear pathophysiologic consequences because the contribution from dying epithelial cells to the loss of organ function becomes greatly amplified by the additional loss of cellular function from proliferating and dedifferentiated epithelium that surrounds the initial sites of injury. Although this speculative "best fit" model has not been investigated directly in CG, preliminary studies to characterize the earliest stages of development of CG in some murine models have found that apoptosis or necrosis of renal epithelium occurs before the aberrant proliferation of renal epithelium becomes apparent (80,84,85,94,118).…”
Section: Models Of Pathogenesismentioning
confidence: 99%
“…These studies have indicated that the product of the HIV gene nef, a gene that is involved in viral replication, is a particularly important contributor to the development of nephropathy, although it is not alone sufficient to produce this injury (9 -11). Murine models in which transgenic expression of HIV is limited to podocytes (resulting from the use of a nephrin promoter construct) have been created recently and show that HIV infection of podocytes is sufficient to produce the CG phenotype of HIVAN (12).…”
Section: Hiv-associated Nephropathymentioning
confidence: 99%